Wind Energy Water Pumping System - Maharasan, M.; Malayali, P.; Murugavel, B.; Raja, Pradeep; Eswaran, A.; Balakrishnan, N. (International Journal For Research In Mechanical & Civil Engineering, 2017)
This project concept is based on mechanical engineering and sustainable development in developing countries. Hence research and analysis has shown that wind energy, solar energy and biomass are the most prominent solutions to the above problems because they are eco-friendly and readily available in nature. Wind Mill is used to generate wind energy . The windmills provide mechanical energy that is used directly on machinery. E g: water pump or wind turbines that provide electrical energy .The covers are in place to prevent soil from clogging the holes, drip irrigation system was not part of this project. A water pumping windmill which can be built largely with materials and skills available in rural areas has been designed and fabricated. The windmill uses a rotor and incorporates a novel sail-type construction. The pump is of a positive displacement type using the casing of a pneumatic type for the pumping chamber. Two prototypes have been constructed and these have indicated a reasonable performance and reliability.